The Comic Strips: Its Usage for Solving Students’ Grammatical Problem in Writing Past Tense - Putri Novitasari (Kirana Publisher (KNPub), 2024)
The objective of this study intended to find out whether there was significance influence of comic strips when it used to help eight grade students for solving their problem in writing past tense. In this research researcher applied comic strips as instructional media to teach them writing. Quantitative research with true-experimental research was implemented as the research design. The sample of this research consist of 34 students from one class of eight grade of junior high school. The result from post test showed that the students’ mean score before taught using comic strips was 57.32 and reached to 77.94 after the teacher apllied comic strips. The result of t-score was 10.493 and the t-table was 1.692 at the level of significance of 0.05. Furthermore, in corelation between hypothesis and data analyzation it can be sumed up that there was significant influence between comic strips and students’ writing in past tense. The increasing of mean score proved that there was improvement on students’ writing skill in composing or writing past tense by applying comic strips as their instructional media for teaching and learning proccess.